Legal Science Methodology through the Lens of Legal Thinking Innovations - GARASYMIV, Taras Z.; PAVLIV-SAMOYIL, Nadiya P.; HODIAK, Andrii I. (Journal of advanced research in law and economics, 2020)
The relevance of the subject matter lies in the low efficiency of generally accepted methods of legal research, the lack of modification and transformation from due to obsolescence and inconsistency with modern tendencies in the development of the legal scientific framework and legal thinking of subjects of such activities. This paper is not limited to the classical methods of cognition, it also touches on the topics of basic legal concepts, theories, and well-known approaches in legal science. The main purpose of this paper is to designate the modern methodology of legal science through the lens of innovations in legal thinking, methods of applying methodological approaches, including an in-depth analysis of research methods in legal disciplines with the use of a comparative analysis of Ukraine and countries of the European economic zone. To achieve this purpose, the following special methods of legal analysis were applied in the scientific paper: analysis, synthesis, generalization, hermeneutic method, historical method, comparative and structural-functional methods. As a result of the study, the already existing methodological approaches will be expressly outlined, as well as those that emerged due to innovations in legal thinking and are capable of covering the features of knowledge of law as a social phenomenon. Furthermore, urgent problems of theoretical and methodological aspects of the study of modern legal systems were identified on the example of different states. One of the successes of the scientific analysis of the methodology of legal science lies in the proposal of methods for conducting complex legal research, described by the features of modernity, relevance, and compliance with the information and technological development of social relations. In addition, the sources regarding the methodology of law in Ukraine and foreign countries are systematized. A historical insight into the becoming of the main tendencies and qualities of the evolution of views on the methodology of law will be the subject of comparative analysis in order to identify new methods of legal cognition. Recommendations regarding the subject matter are expressed in the prospects for further research on the problems of the methodology of legal science and the creation of ways to overcome them. Furthermore, research materials can be used in the preparation of training materials, teaching aids, as well as in the learning process in various areas of legal disciplines.